2017
DOI: 10.1186/s12889-017-4553-8
|View full text |Cite|
|
Sign up to set email alerts
|

Increasing students’ physical activity during school physical education: rationale and protocol for the SELF-FIT cluster randomized controlled trial

Abstract: BackgroundThe Self-determined Exercise and Learning For FITness (SELF-FIT) is a multi-component school-based intervention based on tenets of self-determination theory. SELF-FIT aims to increase students’ moderate-to-vigorous physical activity (MVPA) during physical education lessons, and enhance their autonomous motivation towards fitness activities. Using a cluster randomized controlled trial, we aim to examine the effects of the intervention on students’ MVPA during school physical education.MethodsSecondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 52 publications
(55 reference statements)
0
18
0
Order By: Relevance
“…KS2 children’s focus groups also highlighted a need for younger children to be consulted in designing PA extra-curricular programmes, which offered greater variety: “They might not like it, so they might not want to do it.”; “See what they like the most and start things to do with them.”; “Get the school more active and more sporty and more sports clubs.”; “…and also offer more opportunities for clubs…” This indicates that the opportunities for PA within this particular school encourage PA for older children specifically, and there is a need to consider PA opportunities for younger children. However, the school-based PA findings do support the concept of the school being a supportive platform for PA promotion [ 35 , 36 , 37 , 38 ], and therefore schools are effective locations for staging PA interventions.…”
Section: Discussionmentioning
confidence: 99%
“…KS2 children’s focus groups also highlighted a need for younger children to be consulted in designing PA extra-curricular programmes, which offered greater variety: “They might not like it, so they might not want to do it.”; “See what they like the most and start things to do with them.”; “Get the school more active and more sporty and more sports clubs.”; “…and also offer more opportunities for clubs…” This indicates that the opportunities for PA within this particular school encourage PA for older children specifically, and there is a need to consider PA opportunities for younger children. However, the school-based PA findings do support the concept of the school being a supportive platform for PA promotion [ 35 , 36 , 37 , 38 ], and therefore schools are effective locations for staging PA interventions.…”
Section: Discussionmentioning
confidence: 99%
“…These sessions will highlight the concepts of MVPA (i.e., huff and puff activity), FMS, motivation, and “co-physical activity”. There will be a gameplay period within the session, using innovative tools and methods, such as methods previously developed by Ha, Lonsdale, Lubans and Ng [41]. These will be followed by a skill development period using a set of easy sports equipment, including skipping rope, soft volleyball, sponge flying disc, which will be given to participants for free.…”
Section: Methodsmentioning
confidence: 99%
“…The review revealed studies that advocated the need for programme development and research as evidence to disseminate and implement policies on school health, whereas other studies revealed measures in which the programme and research materials would be the following: delivery of evidence-based information, development of policies and action guides (Chiang et al 2015 :779; Ha et al 2018 :11; Nathan et al 2016 :106; Robinson et al 2014 :S76). However, other studies have revealed that programme manuals have been adopted, and theories have been tested and used as evidence to disseminate and implement a policy on school health; thus, such evidence should be utilised (Chiang et al 2015 :779; Larson et al 2017b:208; Tapia et al 2017 :530; Vanneste et al 2016 :6).…”
Section: Theme 3: Programme Development and Researchmentioning
confidence: 99%